Macroeconomic implications of oil price fluctuations: A regime-switching framework for the euro area - Fédéric Holm-Hadulla; Kirstin Hubrich (European Central Bank (ECB), 2017)
We investigate whether the response of the macro-economy to oil price shocks undergoes episodic changes. Employing a regime-switching vector autoregressive model we identify two regimes that are characterized by qualitatively different patterns in economic activity and inflation following oil price shocks in the euro area. In the normal regime, oil price shocks trigger only limited and short-lived adjustments in these variables. In the adverse regime, by contrast, oil price shocks are followed by sizeable and sustained macroeconomic fluctuations, with inflation and economic activity moving in the same direction as the oil price. The responses of inflation expectations and wage growth point to second-round effects as a potential driver of the dynamics characterising the adverse regime. The systematic response of monetary policy works against such second-round effects in the adverse regime but is insufficient to fully offset them. The model also delivers (conditional) probabilities for being (staying) in either regime, which may help interpret oil price fluctuations - and inform deliberations on the adequate policy response - in real-time.
Keywords: E31; E52; C32; 330; regime switching models; time-varying transition probabilities; oil prices; inflation expectations; inflation